Factors controlling the variation in physicochemical parameters of springs in Melamchi area, Nepal - Khadka, Karishma; Rijal, Moti Lal; Gyawali, Rupak (Journal of Nepal Geological Society, 2023)
Understanding the factors controlling the spatial and seasonal variation of physicochemical parameters of groundwater are important for quick water quality assessment and for a better planning of the water quality management strategies. This study evaluated spring’s five physicochemical data (pH, EC, TDS, DO and temperature) for 75 springs in two seasons (pre and post monsoon). The aim of the research presented in this paper is to assess physicochemical parameters of spring water, understand their seasonal and spatial variation and the factors controlling the variation. Physicochemical parameters were correlated with each other to understand the processes and an attempt has been made to understand groundwater processes studying the physicochemical parameters. Groundwater is slightly acidic to slightly alkaline with pH ranging from 5.5 to 7.5 and is weakly to very weakly mineralized with EC range of 21.6–234.0 μS/cm in pre-monsoon and 10.5–189.8 μS/cm in post-monsoon. TDS ranged between 5.3–116.9 mg/l and 10.8–94.9 mg/l, DO between 3.1–9.4 mg/l and 2.4–7.3 mg/l and groundwater temperature between 18.4–27.9°C and 19.2–27.4°C in pre-monsoon and post monsoon season respectively. TDS and EC are noted to be higher in pre-monsoon whereas pH, DO and temperature are comparatively higher in post-monsoon. The south-east region of the study area shows minimum groundwater temperature. Minimum concentration of EC and TDS were observed in south-east and north-west part of the study area with values increasing towards the river valley. Groundwater temperature shows inverse relation with elevation, pH and DO while correlated with EC and TDS of groundwater in the region. The measured parameters were seasonally and spatially variable. The results indicate difference for measured physicochemical parameters mainly caused due to results generated by cumulative interactions of monsoonal rain, atmospheric temperature, rock-groundwater interaction, residence time of groundwater and seasonal influences. The change in parameters with respect to elevation and relation between different parameters shows shallow aquifer-related groundwater processes.